A Middleware Proposal Towards The Compliance of Small Business Databases with the LGPD - Zerbielli, Yasmin Maria; Felicio, Vinicius Begnini; Solutchak, Cristian; Kunzler, William; Peretti, Gustavo Schwitzki; Ozório, Glória de S. P.; Priesnitz Filho, Walter; Scalco Neto, Heitor (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2023: Anais do XX Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2023.236292, 2023)
This proposal introduces a middleware development solution aimed at enhancing data security measures for small databases, thereby improving data protection compliance with the Brazilian General Data Protection Law (LGPD). The middleware uses MySQL Proxy to intercept traffic between the application and the database. From the data obtained with MySQL Proxy, the middleware extracts the characteristics of the query and applies AES encryption. This proposal aims to make this adjustment process transparent to the user without needing changes in the database or application. The obtained results validate the proposal for applying symmetric cryptography for the data previously stored in the database and new MySQL operations.